Social representations of human rights produced by high school students - de Oliveira, Ricardo Gonçalves Vaz; Pereira, Caroline Rocha [UNESP] (Instituto Rede de Pesquisa Empirica em Direito (REED), 2020)
With the culture and practice of Human Rights in the educational field, it is intended to open spaces for dialogue, criticism, tolerance, understanding and respect for the other, contributing to democratization and otherness in school. It also seeks to provide opportunities for the formation of autonomous subject, aware of their rights and duties, prepared for the full exercise of citizenship. In this sense, the fundamental question that guides this research is: how do high school students represent Human Rights and how are they assimilating their rights and duties in life and in school? The present research is based on the method of analysis of social representations, systematized by Moscovici (2003), Jodelet (2001) and collaborators, which is based on the analysis of participants’ discursive practices, students of high school in a public school. The interviews were recorded, transcribed and systematized through the content analysis procedure (BARDIN, 1979), thus obtaining 10 thematic categories that were analyzed and discussed. In conclusion there is a problem related to the teaching of Human Rights in the School, which comes as a challenge for educators and researchers, whose mission is to develop strategies and methods capable of generating awareness and change of reality.
RepresentaÇÕes sociais de direitos humanos produzidas por estudantes do ensino mÉdio
Keywords: Social representations/ human rights/ school/ violations of rights